Walking Where Jesus Walked : American Christians and Holy Land Pilgrimage - Kaell, Hillary (Book collections on Project MUSE., 2014)
Since the 1950s, millions of American Christians have traveled to the Holy Land to visit places in Israel and the Palestinian territories associated with Jesus's life and death. Why do these pilgrims choose to journey halfway around the world? How do they react to what they encounter, and how do they understand the trip upon return? This book places the answers to these questions into the context of broad historical trends, analyzing how the growth of mass-market evangelical and Catholic pilgrimage relates to changes in American Christian theology and culture over the last sixty years, includi.